Posted by **Roxanne** on Wednesday, March 7, 2007 at 8:36pm.

(2y+1)(y+3)(5y-2)=0

If A x B x C=0, then A, B, or C are equal to zero. Therefore, for the problem, 2y+1=0

y+3=0

5y-2=0

Solving the equations for y will give the correct answers (three of them) for y.

## Answer This Question

## Related Questions

- other Quadratic equations - The problem is 7x^3-x+1=x^3+3x^2+x. Find all real ...
- Precalculus problems check? - Did I do these two problems right? P(1-sqrt2) = 8x...
- Math - Solving Trig Equations - Solve each equation on the interval: 0 is less ...
- Math - ok so i'm kinda sort of confused... I had this for a equation X^2 + 4X - ...
- math - can someone correct these for me. 8x –4y = 16 y = 2x –4 My answer: This ...
- Math - So I'm doing solving system of equations, 2x+y=5 4x+2y=10 I found no ...
- Calculus - Integrals - I made this question, just wanted to make sure it didn't ...
- algebra attn Reiny - Thanks for your help with the solving of the three ...
- Algebra I - Question:The number of students on the football team is two more ...
- Math (Solving Equations) - Find all solutions (answers should be given in ...

More Related Questions